2020
DOI: 10.3389/fgene.2020.00923
|View full text |Cite|
|
Sign up to set email alerts
|

Infrared Spectrometry as a High-Throughput Phenotyping Technology to Predict Complex Traits in Livestock Systems

Abstract: High-throughput phenotyping technologies are growing in importance in livestock systems due to their ability to generate real-time, non-invasive, and accurate animal-level information. Collecting such individual-level information can generate novel traits and potentially improve animal selection and management decisions in livestock operations. One of the most relevant tools used in the dairy and beef industry to predict complex traits is infrared spectrometry, which is based on the analysis of the interaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 188 publications
(231 reference statements)
0
20
0
Order By: Relevance
“…Apart from management perspectives, these prediction models can also be used to generate phenotypes on a large-scale for genetic improvement of metabolic health, a trait that is difficult and expensive to measure (Pryce et al, 2016;Gengler et al, 2018;Bresolin and Dórea, 2020). Using the data of 1,393 Holstein-Friesian cows, Luke et al (2019a) indicated that despite being lowly heritable, with genomic heritability estimates of 0.09, 0.18, and 0.18, for BHB, fatty acids, and urea, respectively, genomic selection of these traits is possible with accuracies ranging between 0.31 and 0.51.…”
Section: Resultsmentioning
confidence: 99%
“…Apart from management perspectives, these prediction models can also be used to generate phenotypes on a large-scale for genetic improvement of metabolic health, a trait that is difficult and expensive to measure (Pryce et al, 2016;Gengler et al, 2018;Bresolin and Dórea, 2020). Using the data of 1,393 Holstein-Friesian cows, Luke et al (2019a) indicated that despite being lowly heritable, with genomic heritability estimates of 0.09, 0.18, and 0.18, for BHB, fatty acids, and urea, respectively, genomic selection of these traits is possible with accuracies ranging between 0.31 and 0.51.…”
Section: Resultsmentioning
confidence: 99%
“…Many different spectrometers have been used for measuring the absorbance of electro-magnetic radiation in meat 1 , 23 , 32 . As well as near-infrared (NIR), ultra-violet 33 , 34 , visible 35 , and mid-infrared 33 , 36 radiations have also been used.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the practical obstacles to establishing a selection scheme for the genetic improvement of meat quality traits have recently been partially offset by the availability of small, portable and robust spectrometers 22 that can collect spectra directly from the meat surface in the working environment (abattoirs, meat processing plants, retail outlets, etc.) without the need to take, transport, preserve and process samples 23 . Portable spectrometers differ greatly in size, spectrum extension and definition, technical features, and cost.…”
Section: Introductionmentioning
confidence: 99%
“…However, FTIR spectroscopy potentially provides better means for exploring subtle chemical distinctions and minor chemical components than NIR. Today, FTIR is widely used in dairy industries for routine analysis for determination of chemical features such as fat, protein, lactose and urea contents [ 12 ]. Information on groups of fatty acids and even main single fatty acids can also be available from the spectra [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Information on groups of fatty acids and even main single fatty acids can also be available from the spectra [ 13 , 14 ]. Studies also indicate use of FTIR in analysis of features such as protein composition, milk coagulation properties, acidity, and milk minerals [ 12 , 15 ]. Considerable efforts have also been put into the development of FTIR spectroscopy for herd management applications such as EB predictions and cow health monitoring.…”
Section: Introductionmentioning
confidence: 99%